1993
DOI: 10.1037/1040-3590.5.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol outcome expectancies: Scale construction and predictive utility in higher order confirmatory models.

Abstract: The goals of this research were to develop a scale to measure alcohol outcome expectancies that incorporated important features suggested by previous research; to examine the psychometric properties of the instrument, with particular attention to item discrimination; and to examine the relationship of positive and negative expectancy to self-reported alcohol use. In Study 1, a preliminary expectancy scale was constructed; factor analysis showed 2 general constructs representing positive and negative consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
302
4
9

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(341 citation statements)
references
References 72 publications
26
302
4
9
Order By: Relevance
“…They provide information about accessible and consequently relevant health cognitions. Such responses are useful for identifying personally relevant issues for qualitative analysis and have been used effectively in questionnaire development (Leigh & Stacy, 1993;Markland & Hardy, 1993;McCarthy, Pedersen, Thompsen, & Leuty, 2006). The present method provides a valid and efficient coding procedure that reduces ambiguity and solves a critical problem in sociates correlate with corresponding levels of alcohol and marijuana use in the population of college students.…”
Section: Discussionmentioning
confidence: 99%
“…They provide information about accessible and consequently relevant health cognitions. Such responses are useful for identifying personally relevant issues for qualitative analysis and have been used effectively in questionnaire development (Leigh & Stacy, 1993;Markland & Hardy, 1993;McCarthy, Pedersen, Thompsen, & Leuty, 2006). The present method provides a valid and efficient coding procedure that reduces ambiguity and solves a critical problem in sociates correlate with corresponding levels of alcohol and marijuana use in the population of college students.…”
Section: Discussionmentioning
confidence: 99%
“…In girls of the youngest subject group 29% of the variance in current drinking was accounted for by the second-order low-dose negative expectancies and age, model ® t: c 2 (19 df) 5 30.6, p 5 0.045. The LISREL VIII output indicated (ª M odi® cation Indicesº , Jo È reskog & So È rbom, 1993) that the speci® c alteration to the model required in this subgroup was a direct path from the residual of sexual± social inhibition to QF (a sim ilar alteration as described in Leigh & Stacy, 1993). For boys in the second subject group, prediction of current drinking was increased to 30%.…”
Section: In Each Of the Six ® Gures The Small Ellipses In The Left Cmentioning
confidence: 96%
“…Expectancies have consistently been found to be associated with current alcohol consumption in college students (e.g. Leigh & Stacy, 1993), com munity samples (e.g. Brown et al, 1980) and adolescents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fromm e, Stroot & Kaplan, 1993;Leigh & Stacy, 1993;C hen et al, 1994; M cM ahon, Jones & O' Donnell, 1994). In addition, it has been shown that expectancies vary with the dose of alcohol concerned (Southwick et al, 1981;Connors et al, 1987;Collins et al, 1990;Earleywine & M artin, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation